Postjugoslovanski spomini kot strategija upora na primeru študije političnega pomena jugonostalgije - Popović, Milica (visokošolska dela, 2021)
Embracing the social-constructivist concept of the past, as introduced by Maurice Halbwachs (Assmann, 2008, p. 55), my research takes an interdisciplinary approach to nostalgia, bringing together political science and cultural memory studies. Valuing the importance of emotions (Nussbaum, 2013; Hassner, 2015) in the political field and acknowledging the ascent of contentious politics (Tilly, 2006; McAdam, Tarrow & Tilly, 2001; Tilly, 2008), in a world where official memory discourses are constructing and reconstructing history, this thesis conceptualizes nostalgia as another contentious expression. The last decade has seen an increase in interest in the history of the socialist period in Yugoslavia. This interest in Yugoslavia and in particular, any positive reflection on the Yugoslav experience, was immediately marked as Yugonostalgia: a catch all phrase for any non negative reference to Yugoslavia. With the dissolution of the country, what was once the hegemonic socialist Yugoslav memory narrative was replaced with a new "democratic" post-socialist anti-Yugoslav memory narrative: the revisionist mainstream public discourse. In the (post)Yugoslav space, within the generation of the last pioneers, reminiscing about Yugoslavia became viewed as subversive, and Yugonostalgia as a refuge for post-socialist subjects' cognitive dissonances.1 Understanding Yugonostalgia as a multidirectional (post)Yugoslav narrative searching for the future through the past the main research question is as follows: What does Yugonostalgia mean for politically active last pioneers and how does it dialogue with their political identities? My primary object of research are the narratives of the generation of the last pioneers (born between 1974 and 1982), in three (post)Yugoslav countries: Slovenia, Croatia and Serbia. Starting with a topic of interest - Yugonostalgia of politically active last pioneers - I dived into the data collection, through political ethnography, interviews and participant observation. Through purposive snowball sampling, over the course of 2017 and 2018, I interviewed 62 political actors within the following parameters: understanding "political activism" as wide and comprehensive as possible, whilst drawing a line at taking part in concrete activities within an organized group for 6 months or longer. Methodological nationalism (Wimmer and Schiller, 2003), which asserts that nation-states are the only units of analysis and a natural form of community, was avoided. Nevertheless, data analysis within the Constructivist Grounded Theory approach (Charmaz, 2014) took into account the specific country context whenever results showed divergences, while allowing us to outline the convergences, along generational and the political lines. Departing from the analysis of the childhood memories of the last pioneers, we unravel what it means for them to be children of socialism. Apparently more politically socialized within their families than within schools, the last pioneers depict a concept of a Yugoslav family, understood in a much larger sense than the "mixed" marriage: encompassing not only the ethno-national diversity, within both nuclear and larger families, but also religious and political diversity, and social mobility. For the right-wing interviewees, their political 1 Cognitive dissonances were first conceptualized by Leon Festinger (1957), an American psychologist, describing a situation when we face contradicting attitudes, beliefs and behaviors - in our attempts to achieve consistency we implement various strategies to lower the mental discomfort that appears through altering some of those attitudes, beliefs and behaviors, socialization is always evidently linked with their paternal heritage, including the awareness of one's ethno-nationality. Other than afew examples, the interviewees have recollection of neither their own awareness of ethno-nationality nor any interethnic tensions between the communities. Their childhood memories, besides being unanimously depicted as happy childhoods, paint the diversity and the richness of various experiences, groups and communities as the biggest value; symbolizing a secure environment, providing possibilities and abundance, not solely focused on consumption. The concept of "a normal life" is colored by the idea and the faith in progress and security, provided by the functionality of the state. The dissolution of the country confronts the last pioneers with a sense of a sudden loss, leading into the unforeseen overnight rupture of their lives, an overarching trope appearing in all narratives. The narratives on the interethnic relations slowly appear. Discrimination against assigned ethno-national communities or parents' professional association with JNA (Yugoslav People's Army) becomes a reality, most notably in schools. Shared memories in all three countries are marked by everybody leaving and, in a number of cases, with the interviewees leaving their homes and becoming refugees. The war trauma brought confusion and meandering attempts by the interviewees to understand these identitarian shifts, often within family quarrels, familial divisions and disrupted friendships. A new normality of violence is recalled vividly, marking the memory on the 1990s. The difference in contexts within the three countries gains traction. As memories of the decade in Slovenia refer to the rest of the Yugoslav wars, for Croatia they are identified with the war and, in Serbia, the whole decade of the 1990s is a marker for wars and the political and economic destruction of the country. Still, all the interviewees were minimizing the traumatic experiences through assertions that, "it was not that bad". Discussing the dissolution and the wars, the last pioneers become more prone to adhering to the revisionist hegemonic discourses. Reflecting upon the reconciliation and rehabilitation mainstream discourses, the last pioneers recognize the need for dialogue and debate but also demand a balanced discussion, which avoids both revisionism and banal nostalgia, as they understand it. For the generation of the last pioneers, ethno-nationalisms and the war were imposed top-down by the then political elites and made possible by a large number of various factors, including the global circumstances of the fall of communism and foreign powers' interests in the region. Acknowledging the new memory politics that were introduced with ethno-nationalisms, the last pioneers take upon two paths: first, resolution of cognitive dissonances and ambivalences through the narratives of singularity, with understanding their experience as exceptional, particular and unique; second, recognizing the political strategic and instrumental use of the term Yugonostalgia. Finally, the last pioneers (re)construct the Yugoslav space, which they continue to feel as their (only) home with the Adriatic Sea being its most prominent symbol. Yet, the feeling of home is largely embedded in the linguistic proximity, leaving Kosovo mostly outside. Without questioning the cultural and economic aspects of the (post)Yugoslav space, a shared perception of the negative present and the consequences of transition transpires in the three countries and across the political spectrum, even if among the center and right-wing political actors some of the explanations relay on the concepts of Balkanism and anticommunism. While Yugonostalgia is perceived as equally producing and obstructing creativity in the present political struggles, Yugoslavism is understood as an important element of the re-imagining of the political space in today's world - acknowledging without hesitation its spatial and cultural elements. Yugonostalgia of the last pioneers primarily serves the purpose of resisting the imposed discontinuity, becoming a collective and a political phenomenon. Generationally changing the location, it finds itself engendering the political potential notably for the new left-wing movements and political parties. The rise of the left-wing movements throughout the (post)Yugoslav space, and their enhanced cooperation, is embedded in investigative reflection into how "it was once" in order to establish the new political ideas for how it "can be once again". Rehabilitation of the socialist ideological positioning often finds itself in parallel with the almost automatic denial of Yugonostalgic views, simultaneously repoliticizing nostalgia, whilst also emancipating from the Western ideological heritage through embracing the Yugoslav one. Nostalgia forges generational communities who are transforming into political generations, transforming the memory of the Yugoslav cause into a memory with a (post)Yugoslav cause (Rigney, 2016), bringing back the idea of progress and hope into the political field of (post)Yugoslavia. As the right-wing and center political choices remain embedded in the concepts of nation-states and ethno-national vision of the world, the new left-wing positionalities turn to internationalist Yugoslav reflections. Understanding generation as a key variable, I have established that the generation of the last pioneers shares a sense of a generation, displaying an existing shared consciousness in all three countries and showing stronger influence on memory narratives than political positionality. The narratives of a lost generation, and the shared sentiment of helplessness in the past and in the present appear in all of my interviews. They clearly delineate themselves from the generation of their parents, for whom they believe that they were given the best years of the Yugoslav past, and their children, whom they believe, do not share the same Yugoslav values. In spatial terms, they believe their generation indeed exists beyond the borders of the newly created nation-states, representing the still existing (post)Yugoslav space. Given the fractures between personal memories and mainstream memory politics, the political shifts into (unsuspected) places of everyday life, cultural attachments, intimate friendships and relationships. Showing the strength of political socialization within families over the experience of war and, further on, the strength of the everyday experience across the borders of new nation-states and ethno-national communities through stable emotional networks and connections, within and outside the families - friend or professional networks and traveling. This thesis helps further understand the important influences on our memory narratives and our political positionality within contentious regions and histories; without providing a final definition of Yugonostalgia, this thesis shows the instrumentality of the term and its use as a discursive strategy for obscuring the Yugoslav past and any Yugoslav future, especially regarding left-wing ideologies. The Yugonostalgic memory narratives of the last pioneers demand an identitarian continuity and make the heterogeneous communities again imaginable, while searching for their own truth about the dissolution of Yugoslavia. Politically productive categories manifest through numerous activities: transmission of basic values to one's children as much asthrough establishment of cooperation networks between political parties in Slovenia, Croatia and Serbia, based on the ideological orientation of the parties and movements in question, rather than on the basis of ethno-national communities. These new solidarity channels represent an important political intervention in the (post)Yugoslav world. Another important element of activism appears as opposition to the hegemonic discourses through commemoration events or the public discourses of the political actors. The thesis shows how any attempt to categorize nostalgia fails; and not because it evades our capacity to understand the multitude of layers and meanings it comprehends, but because we try to deny its political character. It is precisely through the political subjectivity of the nostalgic, who colors his/her nostalgia by its contents, that we can identify the nature of nostalgia. Instead of discarding nostalgia as apolitical, we need to reinstate it as the political and thus expand our own understanding of the political field in the 21st century. The (post)Yugoslav memory narratives of the last pioneers give us an insight into new and unexplored political imaginaries of the (post)Yugoslav space that could be summarized as No state, no nation one space, one identity and the future possibilities of the left-wing imaginaries.
Keywords: Disertacije; jugonostalgija; kolektivni spomin; kulturne študije; Postkomunizem; postsocializem; Sociologija kulture